Towards the reader-text interactive approach to teaching imaginative texts: the case for the integrated English curriculum in Kenya - Lumala, Peter F. Masibo (2007)
In this thesis the concept of Interactive Approach (IA) to the teaching and learning of imaginative texts and language is addressed in the English as a Second Language (ESL) context. As the title suggests the focus of the study was the Integrated English Curriculum (IEC) in Kenya. Although this curriculum was introduced twenty years ago, little has been done to bring about the envisaged integration between the English language and literature at the classroom level. The first chapter describes the background to and the rationale for the study. The second chapter addresses the research setting and explains the current English curriculum in Kenyan secondary schools. The related literature is reviewed in chapter 3 with a special focus on the pedagogical relationship between language and literature and the case for or against integrating the two components. In chapter 4, the methods used during data collection and analysis are presented. The findings of the study as described in chapter 5 affirm that there is the continued use of Traditional Approach (TA) to teaching imaginative texts despite the IEC being in place. This was found to be attributable to the lack of relevant training and the overwhelming focus on examinations by the education system as results from teachers show. The use of the proposed Reader - Text Interactive Approach (RTIA) was positively received by learners as shown by their responses to the interactive exercises. On the basis of these findings, the thesis concludes that there is an urgent need for educators to re-think the way teachers of English are trained in the country and redesign the IEC curriculum materials so that these take into account the integrated curriculum. It is further recommended that RTIA be adopted because the approach was found to have the potential of ensuring that the IEC becomes a reality at the classroom level in Kenya secondary schools.